Determination of gas flow through airway exchange catheters: measured and calculated values and dependence on pressure and entrainment1. (9th May 2015) - YanHong, R.; Ihra, G. C.; Gore, C.
Summary Serious complications have been described during oxygenation of patients with airway exchange catheters, due to catheter malpositioning, accidentally applied high airway pressures or high delivered volumes. In this in‐vitro study, we analysed gas flow through various airway exchange catheters and described its dependence on driving pressure and entrainment. We applied driving pressures between 0.5 and 2.5 bar and observed maximal flow rates of 3.6 l.s−1. Measured gas flow values differed significantly from values calculated according to the Hagen–Poiseuille equation. Although flow restriction in ventilators and small‐bore connectors will limit gas flow, large gas volumes may be unintentionally applied via the airway exchange catheters, leading to serious complications.